Occurrence of Polycyclic Aromatic Hydrocarbons (PAHs) in Sediments from Some Rivers in Hanoi, Vietnam - Phung, Thi Vi; Nguyen, Thuy Ngoc; Truong, Thi Kim; Nguyen, Thi Quynh; Nguyen, Thi Mai; Duong, Hong Anh; Pham, Hung Viet (Old Journal, 2019)
This study investigated the occurrence of polycyclic aromatic hydrocarbons (PAHs) in sediment samples collected from some rivers in Hanoi. The total PAH concentrations varied from 155 to 5505 ng/g. PAH concentrations detected in the present study were mostly less than the existing sediment quality criteria according to QCVN 43: 2012/BTNMT but dibenzo[a,h]anthracene (exceeded allowable limits from 1.13 to 4.69 times). The PAH composition patterns in sediment samples suggest the dominance of high molecular weight compounds and indicate important pyrolytic and petrogenic sources. The results of this study contributed to the data on the occurrence and initial identification of the sources of PAH in sediment samples from some rivers in Hanoi.